Modeling the Impact of Mesoporous Silica Microstructures on the Adsorption Hysteresis Loop - Svidrytski, Artur; Hlushkou, Dzmitry; Thommes, Matthias; Monson, Peter A.; Tallarek, Ulrich (Journal of Physical Chemistry C, 2020)
We present a mean-field density functional theory (MFDFT) study of adsorption and desorption for nitrogen at 77 K in three-dimensional (3D) geometrical models of ordered and random mesoporous silicas obtained by electron tomography. Parameters of the lattice MFDFT model, such as reduced temperature, the ratio between the energies of fluid-solid and fluid-fluid interactions, and the lattice unit size, were investigated to achieve best qualitative agreement with experimental isotherms in the hysteresis region. Equilibrium and metastable equilibrium states were analyzed for 500 pressure values in the range of 0 < p/p0 ≤ 1 for both adsorption and desorption, which allowed us to resolve subtle features of the isotherms. Calculated and experimental isotherms show good agreement in the hysteresis region, identifying type IV(a) isotherms with a H1 hysteresis loop for ordered silicas (SBA-15, KIT-6) and H2(a) hysteresis loop for random silica. Hysteresis loops are particularly narrow and hysteresis branches parallel and almost vertical for the ordered silicas. This indicates homogeneous microstructures of uniform, cylindrical pores and confirms that the SBA-15 silica has a highly interconnected 3D mesopore network, as targeted with its preparation, mimicking the pristine 3D mesopore structure of KIT-6 silica. For the random silica, characterized by a heterogeneous microstructure with many narrow and highly constricted pores, the available phase distributions allowed us to distinguish between pore blocking and cavitation along the desorption branch and to monitor the dependence of cavitation bubble size on relative pressure using image analysis. Complementary calculated desorption scanning isotherms reflect pore evaporation in the ordered silicas as expected from an independent pore model, whereas the representative behavior of dependent pores in the random silica involves pore blocking/percolation.
CRIS-Team Scopus Importer:2020-10-16